Diabetic Retinopathy and Pregnancy - N. V. Pomytkina (Oftalʹmologiâ, 2018)
Purpose: analysis of clinical cases of different course of diabetic retinopathy in pregnancy.Patients and methods. The article presents 5 clinical cases of different course of diabetic retinopathy in pregnancy: absence of manifestation, stable course and progression to macular edema and aggressive proliferation.Results. The reasons for progression of diabetic retinopathy during pregnancy were analyzed. The most important were the compensation of diabetes mellitus in preconception period and throughout pregnancy, the severity of retinopathy, and the presence of concomitant pathology. It is emphasized that timely detection of progression signs of retinopathy and laser coagulation during pregnancy makes it possible to stabilize the course of disease and improve visual prognosis. Thus, the monitoring of pregnant women with diabetes mellitus requires an individual approach and careful dynamic observation during pregnancy and in postpartum period. Timely laser coagulation in progression of retinopathy can contribute to preservation of visual functions.Conclusions. Clinical course of diabetic retinopathy in pregnancy is variable: no manifestation, stabilization, progression. Progression of diabetic retinopathy during pregnancy is determined by many factors, in particular, the compensation of diabetes mellitus in preconception period and throughout pregnancy, the severity and stabilization of retinopathy as results of treatment in preconception period, the presence of concomitant pathology. Timely detection of signs of diabetic retinopathy progression and its treatment, particularly laser coagulation of the retina, during pregnancy allows stabilizing the course of disease. There may be an aggressive course of diabetic retinopathy with progression in postpartum period, in connection with which, active monitoring of patients with retinopathy after childbirth is required.